Iklan Satā’ir Panasonic al-Hawā’īyah Koran Al-Ahrām, Mesir: Analisis Semiotik Peirce - Ulyah Darajah (Al-Ma‘rifah, 2020)
Advertising is text in the form of images or writing to promote an item, service, job opening, and others. Print advertisements (newspapers) are useful for all people who read them. The purpose of this paper is to describe the advertisement about “Satā’ir Panasonic al-Hawā’iyah” (AC cover) contained in Egypt’s Al-Ahrām newspaper. The method used in this paper is a qualitative method with descriptive analysis. The theory used in this research is Charles Sanders Peirce’s Semiotic theory; representamen, object, and interpretant. The results in this study indicates that  (1) in terms of representamen, pink flowers in the advertisement show that what is seen is something that smells nice, soft, and comfortable; (2) the object in the advertisement is all the images and writing contained in the ad; (3) while the interpretant of the advertisement shows that the Panasonic brand AC cover product is fragrant, soft, clean, fresh, and comfortable to use.